2015
DOI: 10.1007/s10459-015-9662-5
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional rhetoric and operational realities: an ethnographic study of rounds in four intensive care units

Abstract: Morning interprofessional rounds (MIRs) are used in critical care medicine to improve team-based care and patient outcomes. Given existing evidence of conflict between and dissatisfaction among rounds participants, this study sought to better understand how the operational realities of care delivery in the intensive care unit (ICU) impact the success of MIRs. We conducted a year-long comparative ethnographic study of interprofessional collaboration and patient and family involvement in four ICUs in tertiary ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…This study revealed that some interactions in rounding discussions are negative. These findings support similar results by (Paradis et al, ) ethnographic study of IDR in an intensive care unit. They found that physicians often projected a dominance over other staff members that made them feel hesitant to participate as equal partners.…”
Section: Discussionsupporting
confidence: 93%
“…This study revealed that some interactions in rounding discussions are negative. These findings support similar results by (Paradis et al, ) ethnographic study of IDR in an intensive care unit. They found that physicians often projected a dominance over other staff members that made them feel hesitant to participate as equal partners.…”
Section: Discussionsupporting
confidence: 93%
“…The use of negation here places ‘doctor’ as the dominant and arguably most legitimate profession, and has the potential to alienate and diminish valuable health care team members. This language reflects the hierarchical nature of health care delivery, which is amplified by care structures that maintain medical dominance despite growing egalitarian beliefs …”
Section: Discussionmentioning
confidence: 99%
“…Our authorship team is composed of an interdisciplinary group that includes one clinician (a physician with previous training in history [CRW]), two sociologists (EP and JCR), an epidemiologist (CC) and a linguist (MP). Collectively, we are committed to more egalitarian relationships in health care, and four of us (CC, CRW, EP and MP) have published accounts critical of doctors’ dominance . Our structured coding scheme and analytic approach were developed to distance ourselves from our previous beliefs and to allow us to look with empirical detachment at the data excerpted from selected articles.…”
Section: Methodsmentioning
confidence: 99%
“…This interpretation of triangulation adopts the view that a single truth (or close to it) about the phenomenon can be found and enhanced by studying the phenomenon from multiple perspectives, which is a positivistic claim. By contrast, one of the strengths of ethnography is that it can highlight the nuances and differences that exist around a particular phenomenon from different stakeholders’ perspectives . (p. 183‐4) From this perspective, collecting data from multiple sources helps develop analytical insights between individuals or social groups, which is aligned with the subjective epistemology of ethnography.…”
Section: Core Considerationsmentioning
confidence: 99%